Management of shoot fly, Atherigona pulla in little millet, Panicum sumatrense - Sasmal, Arundhati (Indian Journal of Plant Protection, 2020)
Field trials were conducted at Centre for Pulse Research (CPR), Berhampur, Odisha University of Agriculture and Technology (OUAT) for two consecutive Kharif seasons of 2013 and 2014 for assessment of different seed treatment chemicals like chlorpyriphos 20% EC @ 10 ml/kg seed, imidacloprid 70WG @ 3 g/kg seed, thiamethoxam 25WG @ 3 g/kg seed, foliar spray of neem oil 1500 ppm (0.15%) @ 1.5 l/ha and neem seed kernel extract NSKE 5% @ 500 l/ha, furrow application of carbofuran 3G @ 1 kg a.i./ ha along with untreated control against the shoot fly, Atherigona pulla, infestation in little millet. Results indicated that the seed treatment with imidacloprid 70WG was the best among the seed treating chemicals and at par with granular application of carbofuran 3G in management of shoot fly on little millet during vegetative stages with highest net return of ` 7910/ha and benefit cost ratio (1.90). Foliar spray of neem oil and NSKE was found to be effective in management of shoot fly infestation during late vegetative and panicle initiation (PI) stage with 8.9% to 10.5% white ear head (WEH).